Brand-specific estimates of influenza vaccine effectiveness for the 2021–2022 season in Europe: results from the DRIVE multi-stakeholder study platform - Stuurman, Anke L.; Carmona, Antonio; Biccler, Jorne; Descamps, Alexandre; Levi, Miriam; Baum, Ulrike; Mira-Iglesias, Ainara; Bellino, Stefania; Hoang, Uy; Lusignan, Simon de; Bonaiuti, Roberto; Lina, Bruno; et al. (Frontiers in Public Health, 2023)
Introduction DRIVE (Development of Robust and Innovative Vaccine Effectiveness) was a European public-private partnership (PPP) that aimed to annually estimate brand-specific influenza vaccine effectiveness (IVE), for regulatory and public health purposes. DRIVE was launched in 2017 under the Innovative Medicines Initiative (IMI) umbrella and has conducted IVE studies from its pilot season in 2017-18 to its final season in 2021-22.In 2021-22 DRIVE conducted four primary care-based test-negative design (TND) studies (Austria, Italy, Iceland, England; covering >1,000 general practitioners), nine hospital-based TND studies (France, Iceland, Italy, Romania, Spain; totaling 21 hospitals) and one population-based cohort study in Finland. In the TND studies, patients with influenza-like illness (primary care) or severe acute respiratory infection (hospital) were enrolled and laboratory tested for influenza using RT-PCR. Study contributor-specific IVE was calculated using logistic regression, adjusting for age, sex and calendar time, and pooled through meta-analysis.In 2021-22, pooled confounder-adjusted influenza vaccine effectiveness against lab-confirmed influenza (LCI) overall and per type and subtype/lineage were produced, albeit with wide confidence intervals (CI). The limited influenza circulation in Europe did not allow the network to reach the optimal sample size to produce precise IVE estimates for all the captured brand. The most significant IVE estimates were 76% (95%CI 23-93%) for any vaccine and 81% (22-95%) for Vaxigrip Tetra among adults ≥65 years old and 64% (25-83%) for Fluenz Tetra among children (TND primary care setting), 85% (12-97%) for any vaccine among adults 18-64 years (TND hospital setting), 38% (1-62%) among children 6 months to 6 years (population-based cohort, mixed setting).Over five seasons, DRIVE collected data on >35,000 patients, more than 60 variables and 13 influenza vaccines. DRIVE demonstrated that estimating brand-specific IVE across Europe is possible, but obtaining sufficient sample size to obtain precise estimates for all relevant stratifications remains a challenge. Finally, DRIVE's network of study contributors and lessons learnt have greatly contributed to the development of the COVID-19 vaccine effectiveness platform COVIDRIVE.